ANALYSIS OF SPECIFIC ANTHROPOLOGICAL CHARACTERISTICS AND COMPARISON BETWEEN AND WITHIN CERTAIN POSITIONS IN A VIP CLOSE PROTECTION TEAM (Security Dialogues, 2024)
The aim of this paper is to present the necessary anthropological features essential for the performance of general and specific jobs, as well as a comparison within and between certain positions in the team for the close protection of VIPs. The aim of the research is the analysis of specific anthropological characteristics, within certain positions and comparisons between certain positions. For the purposes of this work, an expert analysis was conducted in which twenty-four experts from the field of close protection from the region and Europehave participated, who in their career were members of VIP security services for at least 5 years and worked in all positions in the close protection team. The necessary anthropological characteristics were assessed by an expert analysis and a comparison was made between and within the team for close protection of VIPs working at a medium threat level in accordance with the model most often used in the region and Europe. The mentioned model includes a minimum of two vehicles during the security transport of VIPs by motor vehiclesand an average number of agents. The results of this research, after analyzing of specific anthropological characteristics, indicate that there are statistically significant differences in the value of certain factors within certain positions in the team, as well as statistically significant differences in the value of certain factors between certain positions in the team. The results of this research are of crucial importance for the continued improvement of the training and formation of teams that work at an intermediate level of threat, considering the individualities and characteristics of the members of the mentioned team.